2018
DOI: 10.3390/sports6030088
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Genetic Markers in Talent Identification and Athlete Assessment in Elite Sport

Abstract: In elite sporting codes, the identification and promotion of future athletes into specialised talent pathways is heavily reliant upon objective physical, technical, and tactical characteristics, in addition to subjective coach assessments. Despite the availability of a plethora of assessments, the dependence on subjective forms of identification remain commonplace in most sporting codes. More recently, genetic markers, including several single nucleotide polymorphisms (SNPs), have been correlated with enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 135 publications
(194 reference statements)
3
39
1
3
Order By: Relevance
“…The DD and ID individuals showed an increased potential for improved sporting performance. These findings are in agreement with other reports (Gineviciene et al, 2016;Ribas et al, 2017;Weyerstra et al, 2017;Jacob et al, 2018) and can be justified by the high degree of heterogeneity found in the Brazilian population (Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The DD and ID individuals showed an increased potential for improved sporting performance. These findings are in agreement with other reports (Gineviciene et al, 2016;Ribas et al, 2017;Weyerstra et al, 2017;Jacob et al, 2018) and can be justified by the high degree of heterogeneity found in the Brazilian population (Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Our study suggests that individuals with DD and ID genotypes are more predisposed to greater physical strength and power due to the presence of the D allele. Concordantly, our findings are in agreement with the studies made in Australia and Turkey (Ulucan et al, 2015;Jacob et al, 2018). In a Serbian study with female soccer players, there was a high prevalence of the DD genotype, suggesting that individuals with this genotype tend to perform better in soccer (Jeremic et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…International organisations overseeing breeding and racing of Thoroughbred racehorses have been hesitant to promote this use of genetic testing (EFTBA 2016), based on the validity of claims to genetic precursors of superior athletic performance (EFTBA 2016). Similar arguments are made in relation to humans for athletic aptitude (Roth (2012), Loland 2015, Webborn et al 2015, Jacob et al 2018. In equine sport, examples are given of a Melbourne Cup (long distance) winner whom it is reputed would, on the basis of genetic testing, be identified as suitable for sprinting, and of 'one of the best (sprinting) stallions in the world .…”
Section: Ethical Arguments Surrounding Genetic Testing For Desirable mentioning
confidence: 88%